Surface polydopamine modification of bone defect repair materials: Characteristics and applications - Du, Jianhang; Zhou, Ying; Bao, Xiaogang; Kang, Zhanrong; Huang, Jianming; Xu, Guohua; Yi, Chengqing; Li, Dejian (Frontiers in Bioengineering and Biotechnology, 2022)
Bone defect is a common challenge facing the clinical orthopedics. The existing bone defect repair material is hard to achieve satisfactory bone integration between material and bone. Therefore, looking for effective methods to improve bone integration of materials-bone contact surface, then promote bone defect repair become more and more important. Inspired by the super-adhesive proteins of mussels in nature, researchers found that the structure and characteristic of polydopamine (PDA) was similar to the super-adhesive proteins secreted by mussels. Which also possess good biocompatibility, bioactivity, hydrophilic, biological adhesion and thermal stability, especially could promote bone cells adhesion and proliferation. Thus, polydopamine is expected to be used as a surface modification material for bone defect repair materials to improve the effect of bone integration between bone defect repair materials and bone tissue interface. Therefore, in this paper, we reviewed researches related to polydopamine-modified bone defect repair materials, and prospected the future applications of polydopamine-modified bone defect repair materials.